The Types and Impacts of Bullying on Taylor Hillridge in Cyberbully Movie - Nada Putri Sakinah; Anita Jamaris (JEdu: Journal of English Education, 2021)
This research is about the types and impacts of bullying on Taylor Hillridge in Cyberbully movie. The aims of this research are: (1) To find out the types of bullying that the character Taylor Hillridge receives in Cyberbully movie. (2) To find out the impacts of bullying that the character Taylor Hillridge suffers in Cyberbully movie. Researcher used descriptive qualitative method. The result of this research for types of bullying researcher found 6 data of verbal bullying, 2 data of relational bullying, 10 data of cyber bullying. However, for the result of this research for the impacts of bullying researcher found, 1 datum of effects on feelings and behavior, 1 datum of academic impact, 1 datum of psychological impact.